Assessment of detraining through a six-minute walk test in patients with heart disease - Victória Moreira Silva; Vitória Moreira Cintra; Maria de Lourdes da Silva; Joilson Meneguci; Fernando Seiji Silva; Eduardo Elias Vieira de Carvalho; Ana Paula Espindula; Lucina Duarte Novais Silva (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Detraining can partially or completely reduce training-induced metabolic adaptations. However, the duration for which the rehabilitation effects persist after detraining, especially in patients with heart disease, remains unclear. OBJECTIVES: To evaluate the principle of reversibility/detraining in patients with heart disease via the 6-minute walk test (6MWT) after a period of rest. DESIGN AND SETTING: A retrospective cohort study developed at the Rehabilitation Center of the Universidade Federal do Triângulo Mineiro in Uberaba/MG, Brazil. METHODS: This clinical, retrospective longitudinal study involved 20 patients with heart disease who underwent 5 months of supervised cardiac rehabilitation (CR). The mean age of participants was 64.05 ± 9.25 years. The initial rehabilitation was followed by an interruption period and rehabilitation for another 5 months. Functional capacity was assessed using the 6MWT. RESULTS: In the specific analysis of the distance covered, values of P = 0.03 and P = 0.01 were obtained on comparing post-training (669.64 ± 58.80 meters) with post-detraining (640.82 ± 101.23 meters) and post-detraining with post-retraining (650.82 ± 96.28 meters), respectively. No significant difference was observed for the comparison between training and retraining (P = 0.83). CONCLUSION: Cardiovascular rehabilitation positively stimulates functional capacity, whereas detraining significantly reduces it. The 6MWT is effective in measuring changes in physical capacity.